Comparison of different types of fertilizers on growth, yield and quality properties of watermelon (Citrullus lanatus) in the Southeast of Kazakhstan - Aitbayeva Akbope; Berik Zorzhanov; Zharas Mamyrbekov; Damira Absatarova; Birzhan Rakhymzhanov; Meruert Koshmagambetova (Eurasian Journal of Soil Science, 2021)
Over the years, the use of organic materials in farming has reduced due to the increase in the use of chemical fertilizers which are rich in readily available plant nutrients. Intensive use of chemical fertilizers may have depressing effect on yield of watermelon. The field experiment were conducted at the Experimental Clinic of the Laboratory “Selection of vegetable and melon crops” and in the laboratory “Biosafety and Biocontrol of vegetable and melon crops” of Regional Branch “Kainar” of the LLP “Kazakh Research Institute of Fruit and Vegetable Growing” which is located in the foothill zone of the southeast of Kazakhstan, to study the effects of different types of organic fertilizers (cow manure, poultry manure and biohumus) and recommended chemical fertilizer (NPK) on the characteristics of watermelon (growth parameters, yield and quality) of southeast of Kazakhstan. There were significant differences among the treatments in relation to fruit yield of watermelon, growth paremeters and quality properties (dry matter, total sugar, Vitamin C and NO3-N). Recommended fertilizer dose (N90P60K60) had the highest fruit yield of watermelon and growth paremeters followed by manure applied at 40 t ha-1. All the fertilizer treatments had higher yield of watermelon than control. From this study, the use of manure as an organic fertilizer in the cultivation of watermelon could be used as alternative to chemical fertilizer. It is recommended that manure at 40 t ha-1 be adopted for watermelon cultivation in in the Southeast of Kazakhstan.